Human intestinal nematode infections in Sri Lanka: A scoping review. - Nalini Kaushalya Jayakody; Anjana Silva; Susiji Wickramasinghe; Nilanthi de Silva; Sisira Siribaddana; Kosala Gayan Weerakoon (PLoS Neglected Tropical Diseases)
Background Sri Lanka, an island located in South Asia, once experienced a notable prevalence of human intestinal nematode infections (HINIs). With the implementation of control programs, infection prevalence was reduced. Detailed information on prevalence, distribution and temporal trends of HINIs is limited. This review aims to explore Sri Lanka's HINI distribution, trends, diagnostics, control and challenges. Methodology We reviewed published information on HINIs in Sri Lanka in electronic databases, local journals and grey literature from inception to September 2022. Based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-Scr), a systematic strategy was used for searching, screening, reviewing and data extraction. The screening was initiated with a review of titles and abstracts using specific keywords, followed by a full-text screening based on predefined eligibility criteria. A total of 105 studies were included in the review, with 28 selected for pooled prevalence analysis. Principal findings The first nationwide survey in 1924 reported a hookworm infection prevalence of 93.1%. By 2017, soil-transmitted helminth (STH) infection prevalence across the island was 0.97% (ascariasis-0.45%, trichuriasis-0.25%, and hookworm infection-0.29%), and the enterobiasis prevalence between 2003 and 2017 ranged from 0% to 42.5%. Strongyloidiasis had been understudied, with a prevalence of 0.1% to 2%. Over the past two decades, the islandwide pooled HINI prevalence was 13.3%. Within specific demographics, it was 6.96% in the general community, 33.4% in plantation sector, and 11.6% in slum communities. During the colonial period, hookworm infection was the commonest HINI, but ascariasis is now more prevalent. The prevailing data relied solely on microscopy, often utilising single stool smears. Mass deworming programs were widely pursued in the first half of the 20th century, initially targeting antenatal women and schoolchildren, and now focusing on specific community groups. National surveys continue monitoring the three main STH infections. Conclusions The significant reduction in STH prevalence in the country over the past ten decades highlights the effectiveness of public health interventions, particularly mass deworming programs. Despite the success, STH prevalence disparities persist in vulnerable populations like plantation and slum communities, where hygiene and living conditions continue to pose challenges. Reliance on single stool smear microscopy highlights the need for more sensitive diagnostics to better assess infections. Fluctuating enterobiasis prevalence and limited strongyloidiasis data underscore the importance of continued surveillance and targeted interventions for sustained control and eventual elimination. Sri Lanka's experiences and control measures offer valuable insights for low-income countries in South Asia and beyond, particularly in managing HINIs with limited resources.